2008
DOI: 10.1007/s11517-008-0396-x
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal reflexes examined during human gait by ground reaction forces: site and gait phase dependency

Abstract: The objective of this study was to investigate the modulation of the nociceptive withdrawal reflex during gait measured using Force Sensitive Resistors (FSR). Electrical stimulation was delivered to four locations on the sole of the foot at three different time points between heel-off and toe-off. Peak force changes were measured by FSRs attached to the big toe, distal to the first and fourth metatarsophalangeal joints, and the medial process of the calcaneus on both feet. Force changes were assessed in five g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Previous studies [4,8,9,11,14,15,21] demonstrated that computeraided analysis of gait patterns could help the neurologist better understand the mechanism of motor control in the human body, and is also useful for monitoring of progressive neurological diseases. The research group led by Akay, Tamura, and Fujimoto [1,2,27,28] applied the wavelet-based fractal analysis and time-frequency matching pursuit algorithm to acceleration signals recorded during climbing stairs and walking along a corridor, in order to study the gait patterns related to neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [4,8,9,11,14,15,21] demonstrated that computeraided analysis of gait patterns could help the neurologist better understand the mechanism of motor control in the human body, and is also useful for monitoring of progressive neurological diseases. The research group led by Akay, Tamura, and Fujimoto [1,2,27,28] applied the wavelet-based fractal analysis and time-frequency matching pursuit algorithm to acceleration signals recorded during climbing stairs and walking along a corridor, in order to study the gait patterns related to neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The Pedar Ò system (Novel GmbH, Munich, Germany) is one of the systems most commonly used for in-shoe-pressure measurement. In the literature, several studies confirm the accuracy and repeatability in plantar pressure measurement achieved using this system [2][3][4][5][6]. This system was used to investigate plantar pressure distribution in different conditions, for example, between man and woman [7], between right and left foot [8], between young and old people [9] and with regard to subjects walking barefoot or in comfortable shoes [10,11].…”
Section: Introductionmentioning
confidence: 87%
“…The stimulation was delivered through selfadhesive electrodes (AMBU Neuroline 700, Denmark). A reference electrode (7 Â 10-cm electrode, Pals, Axelgaard Ltd., USA) was placed on the dorsal aspect of the foot (Emborg et al, 2009). Each stimulus consisted of a constant current pulse burst of five individual 1-ms pulses delivered at 200 Hz.…”
Section: Evoking the Nociceptive Withdrawal Reflexmentioning
confidence: 99%